Grundrechtsschutz zwischen Karlsruhe und Straßburg : Vortrag, Gehalten VOR Der Juristischen Gesellschaft Zu Berlin Am 13. Juli 2011. - Zimmermann, Andreas (Schriftenreihe der Juristischen Gesellschaft zu Berlin., 2012)
Protection of fundamental rights in Europe takes place in a tense balance between EU law, the Convention on Human Rights, and national constitutions. The author draws potential parallels to the relationship between the Federal Constitutional Court and the European Court of Justice, and proposes a dogmatic model for the complimentary protection of fundamental rights.